Fungal Biorefineries (Fungal Biology,, 2018)
This book covers the applications of fungi used in biorefinery technology. As a great many different varieties of fungal species are available, the text focuses on the various applications of fungi for production of useful products including organic acids (lactic, citric, fumaric); hydrolytic enzymes (amylase, cellulases, xylanases, ligninases, lipases, pectinases, proteases); advanced biofuels (ethanol, single cell oils); polyols (xylitol); single cell protein (animal feed); secondary metabolites; and much more. .